Optimization of iron adsorption by activated carbon derived from banana (Musa acuminata) peel - Decena, Kristyl Jo E. (2017)
Excessive release of iron from septic tanks, sewers and industrial sectors, and irrigated agriculture, causes harmful effects on the environment and public health. This pollution causes change in groundwater quality. Iron in drinking water above the guideline value (0.3 mg/L) may cause vomiting, bleeding, and circulatory disorders. Conventional methods for Fe removal, however, are found to be inefficient or eminently expensive. As such, it has been a major global concern to seek after local and cheaper alternatives. Since activated carbon exhibits effective adsorption capacity for heavy metals in wastewater, hence, this study aimed to prepare banana peel activated carbon (BPAC) and evaluate its efficiency as adsorbent for the removal of Fe from synthetically prepared wastewater by measuring the Fe (II) concentrations using UV-Vis Spectrophotometry. The optimization experiments conducted showed that 50 mg of BPAC and 20 min of contact time was sufficient for adsorption resulting in an optimum adsorbance of 48.4%. This work provides an efficient method with the "low cost" and eco-friendly activated carbon from banana peel as an adsorbent material for the removal of Fe from wastewater.